Microbial isolates and their antimicrobial resistance pattern from endotracheal aspirates: a retrospective observational study over one year at a tertiary care hospital of Bangladesh - Saha, Mili Rani; Rahman, Tanjila; Hasan, Md Rokibul; Islam, KM Shahidul (BIRDEM Medical Journal, 2022)
Background: Emergence of multidrug resistant (MDR) organisms causing ventilator-associated pneumonia (VAP) is an increasing threat with substantial mortality in critically ill patients. Aetiology and treatment of VAP in mechanically ventilated patients can be evaluated by analysis of culture reports periodically for better understanding of microbial isolates and their antimicrobial susceptibility pattern. The present study aimed to analyze the culture and sensitivity pattern of endotracheal aspirates in intensive care unit (ICU) patients. Methods: A hospital-based retrospective study was done in the Department of Microbiology, BIRDEM General Hospital, Dhaka, Bangladesh from January to December, 2019. Data were obtained from the laboratory record book conserved in the Department of Microbiology. Isolates of endotracheal aspirates from 715 patients were identified and their antibiotic susceptibility were (done by standard microbiological methods) recorded. Results: Out of total 715 endotracheal aspirates, growth was obtained from 482 (67.4%) samples. Among the 482 culture positive samples, 714 isolates were identified of which 250 (51.9%) yielded single organism and 232 (48.1%) were double organisms. Among total isolates, 642 (89.9%) were bacteria and 72 (10.1%) were fungi. Gram negative bacilli were mostly isolated organisms (85.6%) followed by fungi (10.1%) and gram positive cocci (4.3%). Acinetobacter sp. (40.6%) was the most prevailing of all isolates followed by Klebsiella sp.(29.4%), Pseudomonas sp. (11.2%), Candida sp. (8.7%), Staph. aureus (3.8%), Esch. coli (2.8%) and Aspergillus sp. (1.3%). Almost all (90-100%) of the Acinetobacter sp., Klebsiella sp., and Esch. coli showed resistance to 3rd generation cephelasporin, aztreonam, amoxicillin-clavulunate and ciprofloxacin and lowest resistance was noted to tigecycline (5.2%, 13% and 0% respectively). Imipenem was found resistant to 97.6%, 77.4% and 30% in Acinetobactersp, Klebsiella sp. and Esch.coli respectively. Resistant pattern of Pseudomonas sp. to ceftazidime (72.5%), aztreonam (81.2%), imipenem (75%), aminoglycosides (70-76%), ciprofloxacin (72.5%), piperacillintazobactum (41.2%) and colistin (11.2%) were also noted. Methicillin-resistant Staph. aureus (MRSA)were 77.8% and 75% Enterococcus sp. showed high level resistance to gentamicin (HLGRE). No vancomycin resistant Staph. aureus(VRSA) or Enterococcus sp. (VRE) was detected in this study. Conclusion: Gram negative isolates were large-scale than any other microorganism. Of them, Acinetobacter sp. was most quotidian followed by Klebsiella sp. Acinetobacter sp. and Klebsiella sp. were highly resistant to different antibiotics including imipenem and piperacillin-tazobactum. High rate of colistin resistant Pseudomonas sp. were also observed. Combined clinical, microbiological and infection control strategies can guide appropriate patient management and antimicrobial stewardship program to combat antibiotic resistance in critical care set up in Bangladesh. BIRDEM Med J 2022; 12(3): 195-200